The Social Functions of Ambonese Malay Pantun in Negeri Haruku, Central Maluku Regency - Mustamu, Fiesta Trifena; Maspaitella, Martha; Latupapua, Falantino Eryk (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study discusses the social functions of Ambonese Malay pantun in the community of Negeri Haruku, Central Maluku Regency. Pantun as an oral tradition is not merely a form of verbal expression but also serves as a medium for transmitting cultural values, social ethics, and collective identity within the community. This study aims to describe the social functions of Ambonese Malay pantun in the social and cultural life of the Haruku community. The research employed a qualitative descriptive method with an ethnographic approach. Data were collected through observation, interviews, documentation, and recording of oral traditions from local informants. The results show that Ambonese Malay pantun in Negeri Haruku functions as entertainment, educational media, social control, communication tool, and cultural preservation medium. Pantun is used in traditional ceremonies, social interactions, and community gatherings as a means of conveying advice, satire, and moral teachings. The study also reveals that pantun reflects the local wisdom and collective values of the Haruku community. Therefore, preserving pantun as an oral tradition is essential to maintain cultural identity and support intergenerational transmission of local knowledge.